Contextual Factors Influencing the Implementation of Self-Assessment in Primary Schools - Ghavidel, Yalda; Vojdani, Hamidreza (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the contextual factors that influence the implementation of self-assessment practices in primary school classrooms from the perspective of educators. A qualitative research design was employed to gain an in-depth understanding of teachers’ and administrators’ experiences with self-assessment. Data were collected through semi-structured interviews with 19 primary school educators from Tehran, selected via purposive sampling to ensure relevance and diversity of perspectives. Interviews were conducted until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis, facilitated by NVivo software. The analysis followed an inductive coding process involving open, axial, and selective coding to identify recurrent patterns and conceptual themes across participants’ narratives. The data analysis revealed three major themes: (1) school-level structural conditions, including leadership support, resource availability, policy coherence, and workload; (2) teacher-related beliefs and practices, such as pedagogical style, assessment literacy, and perceptions of student readiness; and (3) student-centered environmental factors, including classroom culture, peer dynamics, and home-school collaboration. Teachers highlighted both enablers (e.g., professional development and administrative encouragement) and barriers (e.g., large class sizes, conceptual confusion, and high-stakes testing culture) that shaped their implementation of self-assessment. Variations in understanding and execution of self-assessment reflected differing levels of training, motivation, and support systems. The successful implementation of self-assessment in primary schools is highly dependent on contextual variables at the institutional, pedagogical, and interpersonal levels. For self-assessment to function as an effective formative tool, comprehensive efforts must be made to address structural limitations, build assessment literacy, and foster supportive classroom cultures. Policymakers, school leaders, and teacher educators must collaborate to align practice with pedagogical intent.